WTO negotiations on trade facilitation self assessment guide (WTO [Geneva]CH, 2013)
Aims to assist developing and least-developed Members to assess their technical assistance and capacity building support needs and priorities to implement Members' proposals on how to clarify and improve GATT articles V, VIII and X.
Keywords: TRADE FACILITATION